2016
DOI: 10.5924/abgri.44.45
|View full text |Cite
|
Sign up to set email alerts
|

A data filtering to utilizing Human Methylation arrays in genome-wide study of bovine DNA methylation

Abstract: DNA methylation is important for regulating gene expression during many biological processes. There are two popular techniques for detecting genome-wide DNA methylation profiles: next-generation sequencing and DNA arrays. We conducted a pilot study for data filtering using Human Methylation arrays to evaluate the genome-wide methylation profiles using bovine DNA samples. Five tissues of two female Japanese Black cattle were analyzed in this study. We focused on the detection P-value as an indicator of the reli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…After methylation array analysis, informative CpG sites were selected as previously described [17]. Briefly, the fluorescence signal intensities of the methylated and unmethylated alleles were obtained [20].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…After methylation array analysis, informative CpG sites were selected as previously described [17]. Briefly, the fluorescence signal intensities of the methylated and unmethylated alleles were obtained [20].…”
Section: Methodsmentioning
confidence: 99%
“…The BLAST program (http://blast.ncbi.nlm.nih.gov/Blast.cgi) was used to identify the sequences with high similarities for each quality-controlled CpG site on bovine genome sequences (UMD3.1.1), using human probes, as previously reported [17, 18]. Then, the CpG sites located at the restriction enzyme sites for Aci I, Bst UI, Hpy CH4IV, and Taq I were selected within the bovine genome sequences identified by the BLAST search.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was found that analyzing DNA methylation in the mouse genome using Infinium HM27 and HM450 platforms [ 11 ] is feasible. Recently, Kobayashi and Takeda determined the utility of Infinium HM450 BeadChips for analyzing bovine genomic DNA, using the benchmark that useful methylation data with good quality are expected to analyze approximately 50,000 CpG sites (about 10% of all probes) [ 12 ]. These results suggest that the technique can advance genome-wide screening of differentially methylated regions (DMRs) in bovine spermatozoa.…”
mentioning
confidence: 99%